The Significance of Warm Colour in the Quran and Its Roles on Memory Performance - Norwardatun Mohamed Razali (Maʿālim al-Qurʾān wa al-Sunnah, 2020)
Colours are mentioned many times in the Holy Qur’an. Some are mentioned as colours in general, and some of them in specific; yellow, white, black, red, green and blue. Each colour has its special connotations in the Holy Qur’an and among these colours, yellow and red are considered as warm colours. This study aimed to find the significance of warm colours in the Holy Qur’an and its relationship to human psychology; focusing on memory performance. This research had used an inductive approach in terms of selecting Quranic verses; in which yellow and red colour were mentioned. These verses were then analysed by referring to the books of exegetical considerations in order to know the implications of these colours’ usage, as well as referring to psychology books and scientific articles. The research found that yellow and red colour in the Holy Qur’an mostly indicate attracting attention or pleasing viewers. Some examples included the yellow colour in resemblance to the colour of the cow, attention to decay and destruction such as yellow colour in the withering plants, and attention to resurrection like the red colour resembling scene of the Day of Resurrection. This indication in the Holy Qur’an is consistent with psychologists’ discovery; warm colours such as red and yellow are more effective and attractive in the process of transferring information from external to sensory memory, and thus to short-term and long-term memory.